Necklace-shaped heterostructure high-entropy alloy and preparation method thereof

By adding specific elements to the FeCoCrNi-based high-entropy alloy and adopting special cold deformation and aging heat treatment processes, a necklace-like heterostructure is formed, which solves the problem of strength and plasticity balance in high temperature environments and achieves excellent mechanical properties of the alloy in a wide temperature domain.

CN119776711AActive Publication Date: 2025-04-08INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411824272.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-08
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

It is difficult for existing high-entropy alloys to maintain excellent strength and plasticity balance in high temperature environments, and it is difficult for traditional processing technology to form excellent necklace-like heterostructures.

Method used

By adding elements such as Al, Ti, Mo and Ta to the FeCoCrNi-based high-entropy alloy, and using a special cold deformation + multi-step aging heat treatment process, a necklace-like heterostructure high-entropy alloy is formed.

Benefits of technology

It realizes excellent comprehensive mechanical properties at low temperatures, room temperature and high temperatures, including high yield strength, tensile strength and elongation, which significantly improves the stability and reliability of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776711A_ABST
    Figure CN119776711A_ABST
Patent Text Reader

Abstract

The invention relates to the field of materials, and provides a necklace-shaped heterostructure high-entropy alloy which comprises the following chemical components in atomic percent: 18 to 25 percent of Co, 16 to 20 percent of Cr, 16 to 22 percent of Fe, 20 to 30 percent of Ni, 3 to 6 percent of Al, 2 to 5 percent of Ti, 0.1 to 0.8 percent of Mo and 0.1 to 0.5 percent of Ta. The invention relates to a preparation method of a necklace-shaped heterostructure high-entropy alloy. The preparation method comprises the following technological processes: burdening, induction melting, casting molding, homogenization, forging, cold deformation and two-step aging heat treatment. In the smelting process, the raw materials are sequentially put into a crucible according to the melting points from low to high, the vacuum degree in an induction furnace is kept within 0.8 Pa in the smelting process, and after other raw materials are completely melted, low-melting-point alloy materials such as Al and Ti are sequentially added into the crucible in a material hanging mode. The high-entropy alloy with the heterostructure has the advantages that the high-entropy alloy with the heterostructure can provide good comprehensive mechanical properties under complex working conditions, and particularly, the strength and plasticity of the high-entropy alloy in a high-temperature environment are excellently balanced. And a potential solution is provided for the requirements of wide-temperature-range use, high strength and high plasticity in practical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material technology, and in particular to a necklace-shaped heterostructure high-entropy alloy and a preparation method thereof. Background Art

[0002] Since it was first proposed in 2004, high entropy alloys (HEAs) have become a research hotspot in the field of materials science. Unlike traditional alloys, HEAs form a solid solution with a high degree of disorder by mixing multiple elements in equiatomic ratios or nearly equiatomic ratios. This unique design concept has opened up broad prospects for the development of new alloy materials. With the deepening of research, heterogeneous high entropy alloys have gradually become an important research direction. By introducing different phases or microstructures into the material, the mechanical properties of the alloy can be effectively controlled, especially achieving a good balance between strength, plasticity and toughness.

[0003] The significant advantage of heterostructured high-entropy alloys is that they can optimize the mechanical properties of materials through multiple interaction mechanisms. In particular, heterostructures provide unique advantages in the balance between strength and plasticity / toughness. First, the different phases in heterostructured alloys can significantly improve the strength of the alloy through interface strengthening, mutual pinning mechanisms, and deformation coordination. Since different phases (or grain structures) have different hardness and deformation behaviors, heterostructures can effectively enhance the tensile and compressive strength of the alloy through load transfer and dislocation hindrance. In addition, each phase (or grain structure) in the heterostructure can also exhibit different plasticity and toughness characteristics according to specific environmental conditions and loading methods, giving the alloy a stronger resistance to crack growth and better impact resistance.

[0004] Especially in face-centered cubic (FCC) high entropy alloys, the alloys after the introduction of heterogeneous structures can not only improve strength through precipitation strengthening, but also improve their plasticity and toughness. By precisely controlling the size and distribution of the heterogeneous structure, micron- to nanometer-scale strengthening phases can be formed in the alloy. These strengthening phases significantly improve the yield strength of the alloy through the particle strengthening effect, while maintaining good ductility and toughness. This allows heterogeneous high entropy alloys to avoid brittle fracture while maintaining high strength, and improve their stability and reliability under complex working conditions. In addition, the interface and phase interface in the heterogeneous structure alloy, as the main source of deformation, help to maintain the mechanical properties of the material at high temperatures. The high entropy effect and hysteresis diffusion effect in the high entropy alloy not only make the alloy have good high-temperature stability, but also effectively slow down the growth of phase transformation and precipitation strengthening phases, thereby ensuring that the strength and plasticity of the alloy at high temperatures are well balanced. These characteristics make heterogeneous high entropy alloys have a wide range of application potential in high-temperature environments, especially in the fields of high-temperature load-bearing materials and fatigue-resistant materials.

[0005] Therefore, heterostructured high-entropy alloys can significantly improve their plasticity, toughness and fatigue resistance while enhancing material strength, providing new possibilities for a variety of engineering applications, especially in applications under high temperature and complex working conditions, demonstrating excellent performance that traditional alloys cannot match. Summary of the invention

[0006] The purpose of the present invention is to provide a necklace-shaped heterogeneous structure high entropy alloy and a preparation method thereof, by adding Al, Ti, Mo and Ta elements to a non-equiatomic ratio FeCoCrNi series high entropy alloy, and adopting special cold deformation + multi-step aging heat treatment to obtain a necklace-shaped heterogeneous structure high entropy alloy. 2 The introduction of structural intermetallic compounds enables this necklace-like heterostructure high-entropy alloy to obtain excellent comprehensive mechanical properties over a wide temperature range, and can be used as structural materials for use in a wide temperature range.

[0007] The technical solution of the present invention is:

[0008] A necklace-shaped heterostructure high-entropy alloy, wherein the chemical composition range of the necklace-shaped heterostructure high-entropy alloy, in atomic percentage, is: Co: 18-25%, Cr: 16-20%, Fe: 16-22%, Ni: 20-30%, Al: 3-6%, Ti: 2-5%, Mo: 0.1-0.8%, and Ta: 0.1-0.5%.

[0009] A preparation method of a necklace-shaped heterogeneous structure high entropy alloy, the process flow is: batching, induction melting, casting, homogenization, forging, cold deformation and two-step aging heat treatment; the induction melting process controls the oxygen and nitrogen content to prevent the formation of brittle non-metallic inclusions; the melting process is sequentially placed in a crucible according to the melting point from low to high, the vacuum degree in the induction furnace is maintained within 0.8Pa during the melting process, after other raw materials are completely melted, low melting point alloy materials such as Al and Ti are sequentially added into the crucible by hanging; after the raw materials are completely melted, electromagnetic stirring is repeated; the obtained ingot is homogenized and forged.

[0010] The homogenization treatment temperature and time are respectively: 1200-1300°C, and the insulation time is ≥12h.

[0011] The ingot was forged after homogenization, with a forging holding temperature of 1250°C, an initial temperature of 1190°C, a minimum temperature of 1080°C, and repeated upsetting and drawing for more than 5 times; the final sample forging ratio was ≥5, and it was air-cooled to room temperature after forging.

[0012] Before cold rolling / cold drawing / rotary forging, the forged samples were subjected to solution treatment. The specific process was as follows: solution treatment was performed before cold deformation, the sample was kept at 1125°C for 60 minutes, and then cooled to room temperature with water; after solution treatment, the sample was cold deformed on the cold rolling / cold drawing / rotary forging equipment:

[0013] (1) Cold rolling process: The cold rolling temperature is room temperature. The sample is subjected to multiple cold rolling processes. The thickness change of each pass is 2 mm. After 10 passes, the thickness is cold rolled from 40 mm to 20 mm, and the total deformation is 50%;

[0014] (2) Cold drawing process: The cold drawing temperature is room temperature. The sample is subjected to multiple cold drawing processes. The diameter change in each process is 0.3 mm. After 10 processes, the diameter is cold drawn from 10 mm to 7 mm, and the total deformation is 51%;

[0015] (3) Rotary forging process: The rotary forging temperature is room temperature. The sample is subjected to multiple rotary forging processes. The diameter changes by 1 mm in each process. After 10 processes, the diameter changes from 20 mm to 10 mm, and the total deformation is 75%. To ensure that the cold deformation is carried out at room temperature, the sample is placed in water for cooling for 5 seconds after each deformation process.

[0016] The aging process after cold deformation is as follows: the cold deformed sample is kept at 920 °C for 15 min, then the sample is quickly placed in a holding furnace at 760 °C for 4 h, and then water-cooled to room temperature.

[0017] After two-step aging, the alloy structure has a necklace-like grain distribution morphology, in which necklace-like fine grains are distributed on the edges of coarse grains, forming an enveloping grain structure in which fine grains envelop coarse grains.

[0018] The room temperature tensile properties of the obtained necklace-shaped heterostructure high-entropy alloy are: yield strength ≥1100MPa, tensile strength ≥1400MPa, and elongation ≥12%; the -196°C tensile mechanical properties are: yield strength ≥1400MPa, tensile strength ≥1800MPa, and elongation ≥12%; the 650°C tensile properties are: yield strength ≥1000MPa, tensile strength ≥1100MPa, and elongation ≥12%.

[0019] Based on the FeCoCrNi series high entropy alloy matrix, the aim is to develop a heterogeneous high entropy alloy with excellent mechanical properties through composition optimization and experimental exploration. First, by adding elements such as Al, Ti, Mo, and Ta, the composition of the alloy is regulated to optimize its phase composition and microstructure. Through forging + special cold deformation + two-step aging treatment process, the alloy forms a necklace-like heterogeneous structure, which can effectively improve the strength of the alloy and optimize its plasticity and toughness, so that the alloy exhibits excellent comprehensive mechanical properties at low temperature, room temperature and high temperature.

[0020] The advantages and beneficial effects of the present invention are:

[0021] The present invention adopts a special cold deformation treatment method, including cold rolling, cold drawing and rotary forging, to introduce a large number of dislocations into the alloy while retaining the original equiaxed grain boundaries of the alloy, creating conditions for the subsequent regulation of the necklace-shaped grain structure. In this process, the accumulation of dislocations and the evolution of grain boundaries will provide a basis for the subsequent microstructure regulation. Subsequently, a high temperature + low temperature two-step heat treatment process is used to further regulate the microstructure of the alloy. At the high temperature stage, through appropriate annealing treatment, recrystallized fine grains are first formed near the original grain boundaries in the alloy, and the recrystallization inside the grains is blocked by the L1 formed at the same time. 2 The structure of the nanophase is hindered, thus forming a necklace-like grain structure. Subsequently, at the low temperature stage, the nanophase precipitation is further promoted to increase the volume fraction of the nanophase. Through the above process, a necklace-like heterogeneous structure with small grains enveloping large grains is formed in the alloy. Through this series of precise process design and regulation, the final heterostructure high-entropy alloy can provide good comprehensive mechanical properties under complex working conditions, especially in high temperature environments, and obtains excellent strength / plasticity balance. This design idea provides a new direction for the development of high-performance alloy materials, and provides a potential solution for the requirements of wide temperature range, high strength and high plasticity in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The tensile curves of the sample in Example 1 at low temperature of -196°C, room temperature of 25°C and high temperature of 650°C;

[0023] Figure 2 The scanning electron microscope microstructure of the sample in Example 1;

[0024] Figure 3 The tensile curves of the sample in Example 2 at low temperature of -196°C, room temperature of 25°C and high temperature of 650°C are shown;

[0025] Figure 4 The scanning electron microscope microstructure of the sample in Example 2;

[0026] Figure 5 The tensile curves of the sample in Example 3 at low temperature of -196°C, room temperature of 25°C and high temperature of 650°C are shown;

[0027] Figure 6 The scanning electron microscope microstructure of the sample in Example 3;

[0028] Figure 7 The tensile curves of the sample in Example 4 at low temperature of -196°C, room temperature of 25°C and high temperature of 650°C are shown;

[0029] Figure 8 The scanning electron microscope microstructure of the sample in Example 4;

[0030] Fig. 9 The transmission electron microscope morphology of the discontinuously precipitated nano-precipitate phase in the sample of Example 4;

[0031] Fig.10 This is the EBSD result of the necklace-shaped grains of Example 4. DETAILED DESCRIPTION

[0032] The present invention will be further described in the following examples, but the present invention is not limited thereto.

[0033] Example 1

[0034] The nominal composition of the alloy is, by atomic percentage: Fe: 20%, Co: 25%, Cr: 18%, Ni: 28%, Al: 4.6%, Ti: 4.0%, Mo: 0.2%, Ta: 0.2%. According to the atomic ratio of the composition, the raw materials are converted into mass percentage for batching, and each raw material is carefully polished to remove surface impurities. Subsequently, each alloy component is added to the crucible of the induction furnace in order from low to high melting point. The smelting process is carried out in a vacuum environment, maintaining the vacuum degree in the furnace at 0.2Pa until the alloy raw materials are completely melted. Subsequently, electromagnetic stirring is used for refining, the refining time is 1 hour, and five crust remeltings are performed.

[0035] The ingot after smelting will undergo the following hot working and heat treatment processes:

[0036] (1) Homogenization treatment: keep at 1200℃ for 12h;

[0037] (2) Forging: The initial forging temperature is 1190°C, and the upsetting and stretching are repeated 5 times. Then the ingot is forged into a round bar with a forging ratio of 5. After forging, it is naturally cooled to room temperature;

[0038] (3) Solution treatment: After keeping at 1125°C for 60 min, immediately cool it to room temperature with water;

[0039] (5) Aging treatment: The cold-drawn alloy was aged at 920°C for 15 min, then placed in a muffle furnace at 760°C for 4 h, and then water-cooled to room temperature.

[0040] The alloy after aging treatment was processed into specimens, and their tensile mechanical properties were tested at low temperature -196℃, room temperature 25℃ and high temperature 650℃, and metallographic observation was performed on the test samples. Figure 1 The test results of yield strength, tensile strength and elongation are shown in Table 1. Figure 2 Show.

[0041] Example 2

[0042] The nominal composition of the alloy is, by atomic percentage: Fe: 20%, Co: 25%, Cr: 18%, Ni: 28%, Al: 4.6%, Ti: 4.0%, Mo: 0.2%, Ta: 0.2%. According to the atomic ratio of the composition, the raw materials are converted into mass percentage for batching, and each raw material is carefully polished to remove surface impurities. Subsequently, each alloy component is added to the crucible of the induction furnace in order from low to high melting point. The smelting process is carried out in a vacuum environment, maintaining the vacuum degree in the furnace at 0.2Pa until the alloy raw materials are completely melted. Subsequently, electromagnetic stirring is used for refining, the refining time is 1 hour, and five crust remeltings are performed.

[0043] The ingot after smelting will undergo the following hot working and heat treatment processes:

[0044] (1) Homogenization treatment: keep at 1250℃ for 12h;

[0045] (2) Forging: The initial forging temperature is 1190°C, and the upsetting and stretching are repeated 5 times. Then the ingot is forged into a round bar with a forging ratio of 5. After forging, it is naturally cooled to room temperature;

[0046] (3) Solution treatment: After keeping at 1125°C for 60 min, immediately cool it to room temperature with water;

[0047] (4) Cold working: After solution treatment, the alloy is subjected to cold rolling deformation. The specific scheme is as follows: a plate with a thickness of 40 mm is taken from the round bar after solution treatment, and rolled to a thickness of 20 mm through 10 passes, with a total deformation of 50% and a deformation of 2 mm per pass. After each pass, the sample is placed in water for cooling for 5 seconds to ensure that each deformation is carried out at room temperature.

[0048] (5) Aging treatment: The cold-rolled alloy was aged at 920 °C for 15 min, then placed in a muffle furnace at 760 °C for 4 h, and then water-cooled to room temperature.

[0049] The alloy after aging treatment was processed into specimens, and their tensile mechanical properties were tested at low temperature -196℃, room temperature 25℃ and high temperature 650℃, and metallographic observation was performed on the test samples. Figure 3 The test results of yield strength, tensile strength and elongation are shown in Table 1. Figure 4 shown.

[0050] Example 3

[0051] The nominal composition of the alloy is, by atomic percentage: Fe: 20%, Co: 25%, Cr: 18%, Ni: 28%, Al: 4.6%, Ti: 4.0%, Mo: 0.2%, Ta: 0.2%. According to the atomic ratio of the composition, the raw materials are converted into mass percentage for batching, and each raw material is carefully polished to remove surface impurities. Subsequently, each alloy component is added to the crucible of the induction furnace in order from low to high melting point. The smelting process is carried out in a vacuum environment, maintaining the vacuum degree in the furnace at 0.2Pa until the alloy raw materials are completely melted. Subsequently, electromagnetic stirring is used for refining, the refining time is 1 hour, and five crust remeltings are performed.

[0052] The ingot after smelting will undergo the following hot working and heat treatment processes:

[0053] (1) Homogenization treatment: keep at 1200℃ for 12h;

[0054] (2) Forging: The initial forging temperature is 1190°C, and the upsetting and stretching are repeated 5 times. Then the ingot is forged into a round bar with a forging ratio of 5. After forging, it is naturally cooled to room temperature;

[0055] (3) Solution treatment: After keeping at 1125°C for 60 min, immediately cool it to room temperature with water;

[0056] (4) Cold working: After solution treatment, the alloy is subjected to room temperature cold drawing. The specific scheme is as follows: a plate with a thickness of Φ10 mm is taken from the round bar after solution treatment, and cold drawn to a diameter of 7.0 mm by 10 passes (the diameter change in each pass is 0.3 mm). After each pass, the sample is placed in water to cool for 5 seconds to ensure that each deformation is carried out at room temperature.

[0057] (5) Aging treatment: The cold-drawn alloy was aged at 920°C for 15 min, then placed in a muffle furnace at 760°C for 4 h, and then water-cooled to room temperature.

[0058] The alloy after aging treatment was processed into specimens, and their tensile mechanical properties were tested at low temperature -196℃, room temperature 25℃ and high temperature 650℃, and metallographic observation was performed on the test samples. Figure 5 The test results of yield strength, tensile strength and elongation are shown in Table 1. Figure 6 .

[0059] Example 4

[0060] The nominal composition of the alloy is, by atomic percentage: Fe: 20%, Co: 25%, Cr: 18%, Ni: 28%, Al: 4.6%, Ti: 4.0%, Mo: 0.2%, Ta: 0.2%. According to the atomic ratio of the composition, the raw materials are converted into mass percentage for batching, and each raw material is carefully polished to remove surface impurities. Subsequently, each alloy component is added to the crucible of the induction furnace in order from low to high melting point. The smelting process is carried out in a vacuum environment, maintaining the vacuum degree in the furnace at 0.2Pa until the alloy raw materials are completely melted. Subsequently, electromagnetic stirring is used for refining, the refining time is 1 hour, and five crust remeltings are performed.

[0061] The ingot after smelting will undergo the following hot working and heat treatment processes:

[0062] (1) Homogenization treatment: keep at 1200℃ for 12h;

[0063] (2) Forging: The initial forging temperature is 1190°C, and the upsetting and stretching are repeated 5 times. Then the ingot is forged into a round bar with a forging ratio of 5. After forging, it is naturally cooled to room temperature;

[0064] (3) Solution treatment: After keeping at 1125°C for 60 min, immediately cool it to room temperature with water;

[0065] (4) Cold working treatment: After solution treatment, the alloy is subjected to room temperature rotary forging deformation. The specific scheme is as follows: a plate with a thickness of Φ20 mm is taken from the round bar after solution treatment, and rotary forging is performed 10 times to a diameter of 10 mm, with a diameter change of 1 mm per time. After each time, the sample is placed in water to cool for 5 seconds to ensure that each time of deformation is performed at room temperature.

[0066] (5) Aging treatment: The cold-drawn alloy was aged at 920°C for 15 min, then placed in a muffle furnace at 760°C for 4 h, and then water-cooled to room temperature.

[0067] The alloy after aging treatment was processed into specimens, and their tensile mechanical properties were tested at low temperature -196℃, room temperature 25℃ and high temperature 650℃, and metallographic observation was performed on the test samples. Figure 7 The test results of yield strength, tensile strength and elongation are shown in Table 1. Figure 8 Show.

[0068] The mechanical properties of the samples finally heat treated in Examples 1, 2, 3 and 4 at low temperature of -196°C, room temperature of 25°C and high temperature of 650°C are shown in Table 1.

[0069] Table 1 Mechanical properties at low temperature -196℃, room temperature 25℃ and high temperature 650℃

[0070]

[0071] As can be seen from Table 1, a type of non-equiatomic ratio high entropy alloy of the present invention forms multiple scale nanophases in the alloy by alloying Al, Ti, Mo, and Ta, so that the alloy obtains comprehensive mechanical properties at low temperature -196°C, room temperature 25°C, and high temperature 650°C. The conventional processing and heat treatment process (Example 1) has an equiaxed crystal structure. After aging, a large number of lamellar nanophases are formed near the grain boundaries. This nanophase is a discontinuously precipitated nanophase and has the same crystal structure as the internal spherical nanophase (L1 2 structure), such as Fig. 9 The formation of a large amount of grain boundary nanophase will significantly promote the brittleness of the alloy at the intermediate temperature (600-800°C), resulting in an alloy elongation of less than 10%.

[0072] The present invention proposes to obtain a necklace-shaped heterogeneous grain structure of the alloy through a customized cold deformation + two-step aging process, such as Fig.10 As shown in the figure, while maintaining relatively high low-temperature and room-temperature comprehensive mechanical properties, the alloy has a tensile strength of more than 1100 MPa at 650°C and an elongation of more than 10%. The necklace-like heterogeneous structure and a large number of nano-precipitated phases inside have greatly improved the low-temperature, room-temperature and high-temperature comprehensive mechanical properties of the alloy.

[0073] Matters not covered by the present invention are known technologies.

[0074] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A necklace-shaped heterostructure high entropy alloy, characterized in that: The chemical composition range of the necklace-shaped heterostructure high entropy alloy is, in atomic percentage, Co: 18-25%, Cr: 16-20%, Fe: 16-22%, Ni: 20-30%, Al: 3-6%, Ti: 2-5%, Mo: 0.1-0.8%, and Ta: 0.1-0.5%.

2. A method for preparing the necklace-shaped heterostructure high entropy alloy according to claim 1, characterized in that: The process flow is: batching, induction melting, casting, homogenization, forging, cold deformation and two-step aging heat treatment; the induction melting process controls the oxygen and nitrogen content to prevent the formation of brittle non-metallic inclusions; the melting process is put into the crucible in order from low to high melting points, and the vacuum degree in the induction furnace is maintained within 0.8 Pa during the melting process. After other raw materials are completely melted, low melting point alloy materials such as Al and Ti are added to the crucible in turn by hanging; after the raw materials are completely melted, electromagnetic stirring is repeated; the obtained ingot is homogenized and forged.

3. The method for preparing a necklace-shaped heterostructure high entropy alloy according to claim 2, characterized in that: The homogenization treatment temperature and time are respectively: 1200-1300°C, and the insulation time is ≥12h.

4. The method for preparing a necklace-shaped heterostructure high entropy alloy according to claim 2, characterized in that: The ingot was forged after homogenization, with a forging holding temperature of 1250°C, an initial temperature of 1190°C, a minimum temperature of 1080°C, and repeated upsetting and drawing for more than 5 times; the final sample forging ratio was ≥5, and it was air-cooled to room temperature after forging.

5. The method for preparing a necklace-shaped heterostructure high entropy alloy according to claim 4, characterized in that: Before cold rolling / cold drawing / rotary forging, the forged samples were subjected to solution treatment. The specific process was as follows: solution treatment was performed before cold deformation, the sample was kept at 1125°C for 60 minutes, and then cooled to room temperature with water; after solution treatment, the sample was cold deformed on the cold rolling / cold drawing / rotary forging equipment: (1) Cold rolling process: The cold rolling temperature is room temperature. The sample is subjected to multiple cold rolling processes. The thickness change of each pass is 2 mm. After 10 passes, the thickness is cold rolled from 40 mm to 20 mm, and the total deformation is 50%; (2) Cold drawing process: The cold drawing temperature is room temperature. The sample is subjected to multiple cold drawing processes. The diameter change in each process is 0.3 mm. After 10 processes, the diameter is cold drawn from 10 mm to 7 mm, and the total deformation is 51%; (3) Rotary forging process: The rotary forging temperature is room temperature. The sample is subjected to multiple rotary forging processes. The diameter changes by 1 mm in each process. After 10 processes, the diameter changes from 20 mm to 10 mm, and the total deformation is 75%. To ensure that the cold deformation is carried out at room temperature, the sample is placed in water for cooling for 5 seconds after each deformation process.

6. The method for preparing a necklace-shaped heterostructure high entropy alloy according to claim 2, characterized in that: The aging process after cold deformation is as follows: the cold deformed sample is kept at 920 °C for 15 min, then the sample is quickly placed in a holding furnace at 760 °C for 4 h, and then water-cooled to room temperature.

7. The method for preparing a necklace-shaped heterostructure high entropy alloy according to claim 2, characterized in that: After two-step aging, the alloy structure has a necklace-like grain distribution morphology, in which necklace-like fine grains are distributed on the edges of coarse grains, forming an enveloping grain structure in which fine grains envelop coarse grains.

8. The method for preparing a necklace-shaped heterostructure high entropy alloy according to claim 2, characterized in that: The room temperature tensile properties of the obtained necklace-shaped heterostructure high-entropy alloy are: yield strength ≥1100MPa, tensile strength ≥1400MPa, and elongation ≥12%; the -196°C tensile mechanical properties are: yield strength ≥1400MPa, tensile strength ≥1800MPa, and elongation ≥12%; the 650°C tensile properties are: yield strength ≥1000MPa, tensile strength ≥1100MPa, and elongation ≥12%.

Citation Information

Patent Citations

  • Nanometer ultra-fine grain high-entropy alloy and preparation method thereof

    CN107893184A

  • Ni-Co-Al-Cr-Fe series single crystal high-entropy high-temperature alloy and preparation method thereof

    CN110317990A

  • Precipitation strengthening type high-entropy alloy and preparation process thereof

    CN111139391A

  • High-temperature-resistant low-density Ni-Co-Cr-Fe-Al-Ti series high-entropy alloy and preparation method thereof

    CN113718152A

  • High-strength gradient structure FeCoNiCr series high-entropy alloy and preparation method thereof

    CN116287928A